Sustainable Land Productivity and Community Resilience: Micro and Meso-Scale Water Harvesting in Jordan's Rangelands and Rainfed Areas - Dhehibi, Boubaker; Haddad, Mira; Souissi, Asma (International Center for Agricultural Research in the Dry Areas, 2024)
This section should provide a snapshot of the entire document and highlight the most important findings. This working paper highlights the economic and environmental benefits of implementing micro and meso-scale water harvesting (RWH) technologies in Jordan’s arid and semi-arid regions, emphasizing their potential for sustainable water and land management. Technologies analyzed include Vallerani RWH, Marab RWH, and olive farming techniques (soil and stone bunds) tailored to diverse topographical and ecological conditions.